"My mother told me that I should not": a qualitative study exploring the restrictions placed on adolescent girls living with HIV in Zambia. Issue 4 (8th December 2017) - Mackworth‐Young, Constance RS; Bond, Virginia; Wringe, Alison; Konayuma, Katongo; Clay, Sue; Chiiya, Chipo; Chonta, Mutale; Sievwright, Kirsty; Stangl, Anne L
Abstract: Introduction: Adolescent girls in sub‐Saharan Africa are disproportionately affected by HIV due to a range of social and structural factors. As they transition to adulthood, they are recipients of increasing blame for HIV infection and 'improper' sex, as well as increasing scrutiny, restrictions and surveillance. This study used a qualitative and participatory approach to explore the messaging and restrictions imposed on adolescent girls living with HIV in Zambia. Methods: Thirty‐four in‐depth interviews and four participatory workshops were carried out with 24 adolescent girls aged 15 to 19 years old living with HIV in Lusaka, Zambia. Key themes explored included experiences living with HIV, finding out about HIV status, disclosure, experiences with antiretroviral treatment, and support needs. Data were organized, coded and analysed using a grounded theory approach to thematic analysis. This analysis uses data on participants' experiences of living with HIV and their interactions with their parents, guardians and healthcare providers. Results: Family and healthcare providers, partly in a quest to protect both the health of adolescent girls living with HIV and also to protect them from blaming discourse, imposed restrictions on their behaviour around three main topics: don't disclose your HIV status, don't have sex, and don't miss your medicines. These restrictions were often delivered using tactics of fear, and usually disconnected from other options. Participants responded to these messages in several ways, including internalizing the messages, changing their behaviour either to comply with or resist the restrictions, by remaining silent and anxious when restrictions were broken, and developing concerns around their own health and sexual and reproductive aspirations. Participants also sometimes experiencing stigma when restrictions could not be maintained. Conclusions: Restrictive messages were delivered to adolescent girls living with HIV through the broader social discourses of stigma, religion, and global and local narratives about HIV. Programmes aiming to support adolescent girls living with HIV need to work together with parents and healthcare providers to reflect on the impact of sanctioning messages, and to encourage more enabling and empowering messaging for adolescent girls living with HIV.